2004
DOI: 10.1097/00004703-200410000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Biomedical and Environmental Risk Factors for Cognitive Development

Abstract: Sickle cell disease (SCD) is associated with a number of biopsychosocial risk factors for cognitive development. Understanding how these risk factors may interact is important for developing interventions for cognitive functioning. The authors assessed the cognitive abilities of children with SCD (n = 50) and related their performance to anemia severity, socioeconomic status (SES), and their interaction. Demographically matched peers without SCD (n = 36) served as a comparison group. Four areas of cognitive we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
65
2
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 25 publications
5
65
2
8
Order By: Relevance
“…These deficits have previously been observed in children with SCD [14,16,34], although findings in this area have been remarkably inconsistent [3,12,38]. In the present study, a visual working memory measurewas chosenthat is relatively independentofmotor-functioning (N-Back task) and an instrument to assess visuo-motor functioning was included as well (Beery VMI), as was recently recommended [16].…”
Section: Discussionmentioning
confidence: 99%
“…These deficits have previously been observed in children with SCD [14,16,34], although findings in this area have been remarkably inconsistent [3,12,38]. In the present study, a visual working memory measurewas chosenthat is relatively independentofmotor-functioning (N-Back task) and an instrument to assess visuo-motor functioning was included as well (Beery VMI), as was recently recommended [16].…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive deficits among children with sickle cell anemia (SCA) have been reported in a variety of domains, [1][2][3][4][5][6] but deficiencies in intellectual function (IQ) have been the most consistently documented. 3,[6][7][8][9][10] Cognitive dysfunction in SCA appears to worsen with age, 7,11 and individuals with SCA are now living longer.…”
mentioning
confidence: 99%
“…3,[6][7][8][9][10] Cognitive dysfunction in SCA appears to worsen with age, 7,11 and individuals with SCA are now living longer. 12 Unfortunately, few studies have evaluated cognitive functioning or associated structural brain abnormalities in adults with SCA.…”
mentioning
confidence: 99%
“…Ischemic injury to the brain is one of the most devastating complications of SCA, with overt stroke occurring at an overall prevalence of 5% 1 and subclinical infarction occurring in 24%-35% of children on screening MR imaging. 2 While several studies have demonstrated neurocognitive deficits in the presence of overt [3][4][5] and silent stroke, [6][7][8] recent studies of large numbers of neurologically asymptomatic children and adults with SCA have demonstrated that cognitive impairment occurs even in the absence of brain abnormalities on conventional MR imaging. [9][10][11][12] Even though the method of neurocognitive assessment varied in these studies, the shared evidence supports both global IQ deficits, as well as domain specific deficits, in executive function and visual-spatial memory.…”
mentioning
confidence: 99%